A mixed method evaluation of the quasi-experimental yoga-based intervention for the behavioural issues of school-going early adolescents in Jaffna, Sri Lanka - Josephine Thirumagal, S.; Surenthirakumaran, R.; Nalini, S.; Coonghe, P.A.D. (Journal of the College of Community Physicians of Sri Lanka, 2024)
Introduction: Behavioural problems of adolescents, such as anger, impulsivity, hyperactivity and emotional problems is a cross-cutting issue among all communities, religions and cultures around the world. An influx of internet, social media, alcohol and illegal substances in the post-conflict period has led to the existing adolescent behaviour problems in Jaffna, Sri Lanka. Objectives: To find out the quantitative and qualitative impact of a yoga-based intervention in the personal lives of grade 8 children in selected schools in Jaffna, Sri Lanka Methods:A non-randomized controlled trial was carried out in four educational zones over six months during 2017-2018. The trial implemented a yoga-based intervention package: 1) slow breathing for 5-6 minutes, 2) Surya namaskar for 6-8 minutes and 3) mindfulness meditation for 5-6 minutes. The intervention was designed by relevant experts through a desk review. In both intervention and control groups, pre/post quantitative assessments were conducted using the Strength and Difficulty Questionnaire (SDQ) of parents, teachers and students; and three focus group discussions (FGD). Thematic analysis was performed from the recordings of both FGDs. Results: The quantitative analysis indicated that according to parents’ assessments, the emotional issues (p=0.001) along with the total difficulty score (p=0.001) were reduced in the intervention group (n=584). Within the control group (n=499), teachers’ assessments indicated an increase in emotional problems (p=0.001) and a reduction in pro-social scores (p=0.001). The FGD results indicated that most of the students felt that their mind got quietened and that completing school homework was a relatively easy task after the yoga intervention. Conclusions & Recommendations: This yoga-based intervention package appeared to be effective quantitatively in reducing their externalizing and internalizing behaviour issues and qualitatively to motivate them to focus on their studies.
Keywords: Adolescent behavioural problems; Yoga-based intervention package; Focus group discussion